2022
DOI: 10.3389/fcell.2022.831894
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Hidden Mechanisms of Different Prescriptions Treatment for Osteoporosis via Novel Bioinformatics Model and Experiment Validation

Abstract: Osteoporosis (OP) is a systemic disease susceptible to fracture due to the decline of bone mineral density and bone mass, the destruction of bone tissue microstructure, and increased bone fragility. At present, the treatments of OP mainly include bisphosphonates, hormone therapy, and RANKL antibody therapy. However, these treatments have observable side effects and cannot fundamentally improve bone metabolism. Currently, the prescription of herbal medicine and their derived proprietary Chinese medicines are pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…GO enrichment analysis found that a large number of GO biologic processes play key roles in the potential causal relationship from low BMD to OA, such as ossification [ 37 ], cell surface receptor signaling pathway [ 38 ], and cell signaling by WNT [ 39 ]. Using OP mice mode, Wu et al discovered that nine cellular elements, including the cytosol, nucleus, cytoplasm, neuronal cell body, protein complex, caveola, and endoplasmic reticulum, were involved in the anti-OP effects on OA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GO enrichment analysis found that a large number of GO biologic processes play key roles in the potential causal relationship from low BMD to OA, such as ossification [ 37 ], cell surface receptor signaling pathway [ 38 ], and cell signaling by WNT [ 39 ]. Using OP mice mode, Wu et al discovered that nine cellular elements, including the cytosol, nucleus, cytoplasm, neuronal cell body, protein complex, caveola, and endoplasmic reticulum, were involved in the anti-OP effects on OA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our GO analysis revealed that the primary ways in which OA affected OP were via inflammatory response, aging, responses to estradiol, glucocorticoids, and hydrogen peroxide [ 37 ]. The study by Guan et al suggested that XianLing GuBao Capsule ( XLGB ) might treat OP through the PI3K/AKT and MAPK pathways [ 38 ]. Similarly, Xiao et al found that PI3K/AKT/NF-κB and MAPK pathways would be the potential mechanism for XLGB in the treatment of OA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, from a molecular point of view, the TCM formula usually play therapeutic roles via multi-components, multi-targets and the multi-pathways. [42][43][44] Thus, decoding the inherent attribute of complex ingredients and their unclear targets of TCM prescriptions has become an urgent problem to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Fiehnbinbase database ( 18 ) was used for substance qualitative work, including retention time index matching and mass spectrometry matching. Finally, the peaks were removed with the detection rate ≤ 50% in QC samples or the detection rate < 50% or RSD > 30% in each group except the QC group ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…It consists of epimedium, curcuma, Morinda officinalis, angelica, phellodendron, and anemarrhena. It was widely used in the treatment of osteoporosis with a definite curative effect (18)(19)(20)(21). Interestingly, EXD also achieved satisfactory results in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%